2017
DOI: 10.1155/2017/5215413
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of Image Contrast for Thicker and Thinner Objects among Current Intraoral Digital Imaging Systems

Abstract: The purpose is to evaluate the performance of current intraoral digital detectors in detail using a precise phantom and new method. Two aluminum step wedges in 0.5 mm steps were exposed by two photostimulable phosphor plate (PSP) systems—one with automatic exposure compensation (AEC) and the other without AEC—and a CCD sensor. Images were obtained with 3 doses at 60 kV. The effect of metallic material also was evaluated. The contrast-to-noise ratio (CNR) for thinner steps and the low contrast value (LCV) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
(24 reference statements)
1
17
1
Order By: Relevance
“…2 Since AEC produces high-contrast images, it has brought advantages to clinical routine even with variations of the X-ray exposure. 3 Although it has been observed that the presence of materials with high physical density influences the AEC performance, 4 this is not clear in the scientific literature yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Since AEC produces high-contrast images, it has brought advantages to clinical routine even with variations of the X-ray exposure. 3 Although it has been observed that the presence of materials with high physical density influences the AEC performance, 4 this is not clear in the scientific literature yet.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 When evaluating digital systems, a recent study found that high-density materials affect the performance of AEC in image contrast, however, the methodological design of the study did not evaluate this effect on grey values equivalent to the dental tissues. 4 Substantial changes in radiographic density due to the presence of high-density materials during radiographic acquisition in modern digital systems have been observed by dentists in their clinical routine, however, no previous study has assessed the effect of the AEC on the grey values of dental tissues in the presence of a high-density dental material. Therefore, the aim of this study was to investigate the effect of AEC induced by high-density dental materials on dental tissue-equivalent grey values obtained with three digital radiographic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, automatic exposure compensation (AEC) is an observer-independent pre-processing tool that adjusts the grayscale range based on the amount of X-ray reaching the image receptor. 2,3 This prevents important image degradation when exposure factors are not optimum, and has a positive effect on patient dose control. 4,5 The existing scientific literature is rather limited concerning AEC; however, digital systems having AEC have demonstrated greater accuracy in the radiographic diagnosis of carious lesions at inadequate exposure factors.…”
Section: Introductionmentioning
confidence: 99%
“…3 Importantly, in addition to the energy factors that can be adjusted on the X-ray machine, such as exposure time, milliamperage and kilovoltage, the physical properties of the X-rayed object can also affect the amount of radiation reaching the image receptor. Recent in-vitro studies 2,6 have shown that the presence of high-density materials affect the gray values of digital radiographic images; furthermore, radiographic images of specific digital systems obtained at constant exposure factors tend to be much denser (darker) when the AEC is triggered by metallic materials. From a clinical perspective, dental practitioners should be aware that any factor affecting the final image quality must be tested to determine how well it has performed several different diagnostic tasks, before it can be used in the clinical routine, regardless of the manufacturer's claim that such a tool was developed to improve the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Although the indirect type of digital sensor, such as the photostimulable phosphor (PSP), is an alternative in digital systems, it does not outperform CMOSs and CCDs in terms of percentage of correct assessment due to contrast and spatial resolution, 16 17 reliable images for root canal working length estimation, 18 and its performance when coupled with automatic exposure compensation. 19 However, PSPs are preferable in academic institutions, where the monitoring of image repetition is more vigorous compared to CMOS and CCD types.…”
Section: Introductionmentioning
confidence: 99%